MECHANICAL IMPACT ON THE CELL COVERING FINE STRUCTURE OF DINOFLAGELLATES PROROCENTRUM MINIMUM - Berdieva, M A; Skarlato, S A; Matantseva, O V; Pozdnyakov, I A (T͡S︡itologii͡a, 2016)
Complex cell coverings (amphiesma) of potentially toxic dinoflagellates Prorocentrum minimum include plasma membrane and flattened amphiesmal vesicles with thecal cellulose plates. Two largest thecal plates surround the major portion of dinoflagellate cell as shell valves. We have revealed that P. minimum cells appear to be extremely sensitive to the physical stress: even low speed centrifugation (1200 and 2000 g) leads to a dropping of old coverings shedding (ecdysis) and the formation of viable spheroplasts. Spheroplasts are surrounded only by the plasma membrane beneath which the new amphiesma is formed. These spheroplasts can be a convenient model system for investigation of numerous aspects of cell and molecular biology of the dinoflagellates.